Aufschwung bleibt moderat — Wirtschaftspolitik wenig wachstumsorientiert - Ferdinand Fichtner; Roland Döhrn; Oliver Holtemöller; Timo Wollmershäuser (Wirtschaftsdienst, 2016)
Die deutsche Wirtschaft befindet sich in einem moderaten Aufschwung. Zu diesem Ergebnis kommt die Mitte April veröffentlichte Gemeinschaftsdiagnose der Wirtschaftsforschungsinstitute. Das Bruttoinlandsprodukt dürfte demnach in diesem Jahr um 1,6% und im kommenden Jahr um 1,5% zulegen. Getragen wird der Aufschwung vom privaten Konsum, der vom anhaltenden Beschäftigungsaufbau, den spürbaren Steigerungen der Lohn- und Transfereinkommen und den Kaufkraftgewinnen infolge der gesunkenen Energiepreise profitiert. – – The German economy is experiencing a moderate upturn. Gross domestic product is expected to increase by 1.6 per cent this year and by 1.5 per cent in 2017. The upturn will be driven by private consumption, which will benefit from continued employment growth, sizeable increases in wage and transfer income, and also purchasing power gains thanks to lower energy prices. Fiscal policy will also be expansively oriented, partly due to rising costs related to refugee immigration. Public budgets will still post significant surpluses in the forecasting period, however. Failing to use this room for manoeuvre to promote growth, as seen in recent years, is not a sustainable path. In view of the continuous slack in the euro area economy, the monetary policy stance is considered to be appropriate. Should it become obvious in the course of this year that production does not return to normal capacity and that the inflation rate does not move towards two per cent, further measures to stimulate growth might become necessary. The scope for further monetary policy measures has been widely exhausted, though. A further economic stabilization could only be achieved through a combination of expansionary fiscal and monetary policy. This could severely damage the credibility of monetary policy, however.
Keywords: E27; E32; E37; 330; Konjunktur; Frühindikator; Deutschland